In-depth comparison of commercial Trichoderma-based products: integrative approaches to quantitative analysis, taxonomy and efficacy - Kulik, Tomasz; Staniszewska, Paulina; Wiśniewski, Patryk; Treder, Zofia; Przybylski, Maciej; Wrońska, Ewa; Maździarz, Mateusz; Krawczyk, Katarzyna; Bilska, Katarzyna; Paukszto, Łukasz; Olszewski, Jacek (Frontiers in Microbiology, 2025)
Products derived from Trichoderma fungi, primarily marketed as biofungicides and biofertilizers, are widely utilized to promote sustainable and regenerative farming practices. In this study, we characterized Trichoderma-based products currently available in both international and local (the Polish) markets. We estimated the number of viable cells in these products, which is a key factor boosting their efficacy. We found substantial differences in the number of colony-forming units (CFUs) among various products, with all products exhibiting fewer CFUs than claimed. The degree of this inconsistency was notably heightened in the case of biofertilizers. We also determined the species identity of isolates recovered from these products using MIST approach. For most products, results of the multilocus species identification revealed inconsistency with taxonomic classification available on product labels or failed to confirm their taxonomic status. We also assessed variation in the invasion capacity of Trichoderma isolates against economically important plant pathogens B. cinerea, F. graminearum and S. sclerotiorum using in vitro approaches. To address the identified challenges associated with the suboptimal quality of biofertilizers, various targeted solutions are discussed and proposed.